4(t+23)-1=7-(3t+8)

Simple and best practice solution for 4(t+23)-1=7-(3t+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(t+23)-1=7-(3t+8) equation:



4(t+23)-1=7-(3t+8)
We move all terms to the left:
4(t+23)-1-(7-(3t+8))=0
We multiply parentheses
4t-(7-(3t+8))+92-1=0
We calculate terms in parentheses: -(7-(3t+8)), so:
7-(3t+8)
determiningTheFunctionDomain -(3t+8)+7
We get rid of parentheses
-3t-8+7
We add all the numbers together, and all the variables
-3t-1
Back to the equation:
-(-3t-1)
We add all the numbers together, and all the variables
4t-(-3t-1)+91=0
We get rid of parentheses
4t+3t+1+91=0
We add all the numbers together, and all the variables
7t+92=0
We move all terms containing t to the left, all other terms to the right
7t=-92
t=-92/7
t=-13+1/7

See similar equations:

| -3+x+10=2x-1 | | 30x=60x-240 | | (x-6)^2=29 | | (4x+10)+(5x)=180 | | -1x-3=8 | | -20=11m | | 13x+23=4 | | 14x+4=40+5x | | 3x+7=2-8 | | k2=49/81 | | T=3m+19 | | X-5=1-x= | | 13(18+12q)=6(2q-7) | | 0.875b-32=0.75+32 | | 3d-2d=1 | | d-8/(-2)=(12) | | 2k^2-7=119 | | 12r=40.5r-1 | | -6=n|2-10 | | 12m+9=27 | | 4-2x=3-3x= | | 1/4(8x+24)=2x+4 | | 180=(6x+7)+(4x+9)+(3x+8) | | 2y-7=2y+5 | | 8(x-11)-16=-56 | | 180=(6x+7)(4x+9)+(3x+8) | | (4x-6)+12=54 | | 8(x-11)-16=56 | | (m+9)/5=2 | | 5k​−5=6 | | 24+7x=4x+12 | | 5x-3x+9=-8+4x+11 |

Equations solver categories